Stock Market Dynamics and Jakarta Islamic Index Returns: An ARDL Approach - Suhendar, Adhatya Rizky; Suriani, Suriani (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2025)
Understanding the factors that influence stock returns is crucial for investors, particularly the Islamic capital markets. This study examines the impact of company size and key financial fundamentals—return on assets (ROA), debt-to-equity ratio (DER), and earnings per share (EPS)—on stock returns in the Jakarta Islamic Index (JII). Using secondary data from seven companies listed in the JII between 2011 and 2021, this study employs the Autoregressive Distributed Lag (ARDL) model to analyze both short-term and long-term effects. The findings indicate that, in the long run, company size and ROA have a positive impact on stock returns, while the debt-to-equity ratio has a negative effect. However, in the short term, ROA negatively affects stock returns, whereas the debt-to-equity ratio has a positive impact. Interestingly, EPS does not influence stock returns in either the short or long term. These results highlight the importance of maintaining strong financial fundamentals to sustain investor confidence in Sharia-compliant stocks. Companies should focus on enhancing financial stability and risk management to attract and retain long-term investors.======================================================================================================== ABSTRAK - Dinamika Pasar Saham and Retur pada Jakarta Islamic Index: Pendekatan ARDL. Memahami faktor-faktor yang memengaruhi return saham sangat penting bagi investor, terutama di pasar modal syariah. Penelitian ini menganalisis pengaruh ukuran perusahaan dan rasio fundamental keuangan utama—return on assets (ROA), debt-to-equity ratio (DER), dan earnings per share (EPS)—terhadap return saham pada Jakarta Islamic Index (JII). Penelitian ini menggunakan data sekunder dari tujuh perusahaan yang terdaftar di JII selama periode 2011–2021. Untuk menganalisis dampak jangka pendek dan jangka panjang, penelitian ini menerapkan model Autoregressive Distributed Lag (ARDL). Hasil penelitian menunjukkan bahwa dalam jangka panjang, ukuran perusahaan dan ROA berpengaruh positif terhadap return saham, sementara debt-to-equity ratio memiliki dampak negatif. Namun, dalam jangka pendek, ROA berpengaruh negatif, sedangkan debt-to-equity ratio berpengaruh positif terhadap return saham. Menariknya, EPS tidak berpengaruh terhadap return saham, baik dalam jangka pendek maupun jangka panjang. Hasil ini mengindikasikan pentingnya mempertahankan fundamental keuangan yang kuat untuk menjaga kepercayaan investor terhadap saham berbasis Syariah. Oleh karena itu, perusahaan perlu meningkatkan stabilitas keuangan dan strategi manajemen risiko guna menarik dan mempertahankan investor jangka panjang